Two new freshwater eutardigrade species from Sicily - Pilato, Giovanni; Sabella, Giorgio; Lisi, Oscar (Zootaxa, 2015)
Two new species of freshwater Eutardigrada are described from Sicily: Isohypsibius rusticus sp. nov. and Isohypsibius zappalai sp. nov. The former species has eye spots, ornamented body surface with many, variously sized tubercles; bucco-pharyngeal apparatus of the Isohypsibius type; pharyngeal bulb with apophyses and two rod-shaped macroplacoids; microplacoid absent; claws, of the Isohypsibius type, well developed, with long and thin common basal portion; main branches of all claws without free accessory points; very thin lunules present; cuticular bars on the legs absent.         Isohypsibius zappalai sp. nov. has eye spots; entire body surface with small tubercles rounded in shape, fairly uniformly sized and tending to form transverse lines; bucco-pharyngeal apparatus of the Isohypsibius type, pharyngeal bulb with apophyses and two macroplacoids; microplacoid absent; claws of the Isohypsibius type, well developed, with long common basal portion and both main and secondary branches with a wide proximal portion. Main branches of all claws with accessory points; small, flexible lunules present; cuticular bars on the legs absent.